Field tests on rate sensitivity of vertical strength and deformation of first-year columnar-grained sea ice - Sinha, N. K. (The Conference, 1983)
Observations on rate sensitivity of uniaxial, unconfined compressive strength and deformation of freshly recovered columnar-grained first-year sea ice are described. Loads were applied parallel to the axis of the columns over a wide range of displacement rates, using a portable test machine in a field laboratory at Mould Bay in the western High Arctic of Canada. Results are analysed in terms of measured stress and strain rate to peak stress. Strengths up to 16 MN.m[-2] at -10 degrees C were obtained, with failure strains in the range of 0.1 to 0.3 per cent. Dans cette note on présente les résultats d'essais de deformation et de résistance à la compression uniaxiale d'échantillons de glace de mer columnaire de première année. Les charges ont été appliquées parallèlement à l'axe des colonnes-échantillons avec plusieurs vitesses de déplacement à l'aide d'une machine d'essai portative d'un laboratoire situé à Mould Bay dans l'Ouest de l'Arctique canadien. Les résultats sont analysés en fonction du taux mesuré de contrainte et de déformation jusqu'aux contraintes maximales. On a obtenu des résistances allant jusqu'à 16 MN. m[-2] à -10 degrés C, avec des déformations de rupture de l'ordre de 0,1 à 0,3 p. cent. Peer reviewed: Yes NRC publication: Yes